PENYELESAIAN KONFLIK DAN KETEGANGAN SOSIAL PERSPEKTIF HUKUM ISLAM - Dr. Sukardi Paraga (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2015)
This article describes the problem settlement komflik and social tensions in the perspective of Islamic law. From the results pemamaparan with sociological approaches and gained an understanding of Islamic law that conflicts and social tensions that often occur in Indonesia, caused by various factors, namely discrimination, differences in character, tribal, or ethnic, the struggle for economic resources. Social conflicts can be prevented by the teachings of their respective religions adherents properly, among others, mutual respect and respect, not mutual fissure or make inter-religious or belief, always developed a sense of unity, compassion and humanity as well as look all human beings equal in the eyes of Allah. Settlement of social conflicts in Islamic law can be done by: 1) Conduct reconciliation (keefing) or the desire to make peace between the two sides of the conflict, 2) Generating a third party who is competent (Hakam or arbitrator), which carry the mandate to try to reconcile end finish social problems that occur. 3) Fight those who violate the peace agreement. In the sense for those who violate the peace agreement and to keep the anarchist action or attack against any other party, then the attack should immediately be taken according to the procedures applicable law.